2020
DOI: 10.1590/1806-9282.66.9.1258
|View full text |Cite
|
Sign up to set email alerts
|

Is the COVID-19 disease associated with de novo nephritic syndrome?

Abstract: SUMMARY INTRODUCTION: This study aims to determine the incidence of de novo nephritic syndrome (NS) in COVID-19 patients and identify its associated factors. METHODS: All ward patients with COVID-19 pneumonia were investigated. After determining the inclusion and exclusion criteria, the study population was identified. The urine dipstick test and urine protein creatinine ratio (UPCR) measurements were performed. Patients with de novo NS findings, nasopharyngeal swab, and urine RT-PCR tests were performed sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
0
0
4

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
2
0
0
4
Order By: Relevance
“…Our ndings revealed that the positive urine SARS-CoV-2 RNA RT-PCR was less common (7 out of 100 patients) in our study population and all of them turned to negative at the time of discharge. Our result was in accordance with studies in Turkey and China that demonstrated nearly 5-7% of COVID-19 patient had positive urine RT-PCR [23,24].…”
Section: Discussionsupporting
confidence: 92%
“…Our ndings revealed that the positive urine SARS-CoV-2 RNA RT-PCR was less common (7 out of 100 patients) in our study population and all of them turned to negative at the time of discharge. Our result was in accordance with studies in Turkey and China that demonstrated nearly 5-7% of COVID-19 patient had positive urine RT-PCR [23,24].…”
Section: Discussionsupporting
confidence: 92%
“…The present findings revealed that positive results of urine SARS-CoV-2 RNA RT-PCR were less common (found in 7/100 patients) in our study population, all of which became negative at the time of discharge. This result is consistent with previous studies from Turkey and China, which demonstrated that nearly 5-7% of COVID-19 patients had positive urine RT-PCR results [24,25].…”
Section: Discussionsupporting
confidence: 93%
“…O contexto pandêmico global provocado pelo vírus SARS-Cov-2 (COVID-19) teve início em dezembro de 2019 na China, na cidade de Wuhan, província de Hubei e, em março de 2020, foi oficializado pela World Health Organization (WHO) (DUARTE et al,2020;DHEIR et al,2020). A doença causada pelo COVID-19, inicialmente provoca uma síndrome respiratória de sintomatologia leve na maioria dos pacientes que evolui para um quadro gripal, entretanto uma parcela desses pacientes tem seu quadro agravado (DHEIR et al,2020).…”
Section: Introductionunclassified
“…O contexto pandêmico global provocado pelo vírus SARS-Cov-2 (COVID-19) teve início em dezembro de 2019 na China, na cidade de Wuhan, província de Hubei e, em março de 2020, foi oficializado pela World Health Organization (WHO) (DUARTE et al,2020;DHEIR et al,2020). A doença causada pelo COVID-19, inicialmente provoca uma síndrome respiratória de sintomatologia leve na maioria dos pacientes que evolui para um quadro gripal, entretanto uma parcela desses pacientes tem seu quadro agravado (DHEIR et al,2020). O comprometimento respiratório, imune e hematopoiético leva à progressão da doença para um quadro de Síndrome do Desconforto Respiratório Agudo (SDRA) associada ao risco de lesões extrapulmonares, principalmente renal, colocando tais pacientes circunscritos a uma alta taxa de mortalidade (DHEIR et al,2020;DUARTE et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation